Assessment Literacy of EFL Teachers in Badung, Bali, Indonesia: Conception and Practices - Isidorus Bagus Geovenda Nyudak (ELT Worldwide: Journal of English Language Teaching, 2022)
Teachers’ assessment literacy is defined as teachers’ knowledge, conception, and skills in administering classroom assessment practices. By the excellent assessment literacy, teachers could maximize students’ learning outcomes. Concerning the essential roles of teachers’ assessment literacy in instructional activities, the present study describes EFL teachers’ assessment literacy in Badung Regency, Bali. The researcher utilizes a descriptive research design, in which the required data is collected from a questionnaire and interviews. Forty-two EFL teachers responded to the questionnaire containing thirty items and then analyzed statistically and descriptively. Four representative subjects are invited to the interviews to confirm and elaborate on how EFL teachers put their assessment literacy into practice in the following stages. The present study found that the general level of EFL teachers’ assessment literacy is fair. Teachers’ professional experience, motivation, professional development, and social are essential in improving their assessment knowledge and practices.